A QUALITATAIVE-QUANTITATIVE STUDY OF MEDIA POLITICAL DISCOURSE FROM THE PERSPECTIVE OF MANIPULATION - Harutyunyan, Rafayel (Armenian Folia Anglistika, 2022)
A survey-based qualitative-quantitative study of manipulation as a psycholinguistic phenomenon provides a good overview of statistical significance and knowledge. The use of qualitative-quantitative research methods in the current study can help us gain a more profound understanding of how people are able to perceive and detect cases of language manipulation. It appears necessary to emphasize that using the methods of qualitative-quantitative research, we can not only assess the respondents’ opinions about "manipulation”, its linguistic and extra-linguistic expression, but also accurately determine and accumulate the obtained knowledge and data about the phenomenon. The paper summarizes and concludes the results of the selected questions in the online questionary which can assist individuals in acquiring information for researches in the same or related fields.
Keywords: manipulation, media - political discourse; qualitative-quantitative study; online survey software; questionary; manipulative language; data